Oviductal structure and ultrastructure of the Oviparous Gecko, Hemidactylus Mabouia (Moreau De Jonnès, 1818) - Nogueira, Katiane de Oliveira Pinto Coelho; Rodrigues, Sirlene Souza; Araújo, Vinícius Albano; Neves, Clóvis Andrade (The Anatomical Record, 2010)
Lizards of the family Gekkonidae display a variety of reproductive patterns, as evidenced by the presence of viviparous and oviparous species. The species Hemidactylus mabouia is oviparous. We examined, in vitellogenic females, oviductal structure by light microscopy after routine histological and histochemical techniques, as well as by scanning and transmission electron microscopy. The oviduct is composed of four different regions: the infundibulum, which opens into the coelomic cavity and receives the oocyte released at the time of ovulation; the uterine tube, where sperm storage takes place; the uterus, which is responsible for the eggshell production; and the vagina, the final portion of the oviduct that leads to the cloaca. The oviductal structure of H. mabouia is similar to that of other oviparous lizard species and can be useful for morphological comparative analysis among reptile species.
Keywords: Oviduct; Reproductive biology; Squamata; Ultrastructure